Extended endoscopic endonasal transsphenoidal approach for retrochiasmatic craniopharyngioma: Surgical technique and results - Sankhla, Suresh K. (J Pediatr Neurosci, 2015)
OBJECTIVE: Surgical treatment of retrochiasmatic craniopharyngioma still remains a challenge. While complete removal of the tumor with preservation of the vital neurovascular structures is often the goal of the treatment, there is no optimal surgical approach available to achieve this goal. Transcranial and transsphenoidal microsurgical approaches, commonly used in the past, have considerable technical limitations. The extended endonasal endoscopic surgical route, obtained by removal of tuberculum sellae and planum sphenoidale, offers direct midline access to the retrochiasmatic space and provides excellent visualization of the undersurface of the optic chiasm. In this report, we describe the technical details of the extended endoscopic approach, and review our results using this approach in the surgical management of retrochiasmatic craniopharyngiomas. METHODS: Fifteen children, including 9 girls and 6 boys, aged 8 to 15 years underwent surgery using extended endoscopic transsphenoidal approach between 2008 and 2014. Nine patients had a surgical procedure done previously and presented with recurrence of symptoms and regrowth of their residual tumors. RESULTS: A gross total or near total excision was achieved in 10 (66.7%) patients, subtotal resection in 4 (26.7%), and partial removal in 1 (6.7%) patient. Postoperatively, headache improved in 93.3%, vision recovered in 77.3%, and the hormonal levels stabilised in 66.6%. Three patients (20%) developed postoperative CSF leaks which were managed conservatively. Three (20%) patients with diabetes insipidus and 2 (13.3%) with panhypopituitarism required long-term hormonal replacement therapy. CONCLUSIONS: Our early experience suggests that the extended endonasal endoscopic approach is a reasonable option for removal of the retrochiasmal craniopharyngiomas. Compared to other surgical approaches, it provides better opportunities for greater tumor removal and visual improvement without any increase in risks.